Assessment of sensory properties and in vitro antimicrobial activity of monofloral Sicilian honey. (April 2023) - Russo, Nunziatina; Di Rosa, Ambra Rita; Pino, Alessandra; Mazzeo, Gaetana; Liotta, Luigi; Caggia, Cinzia; Randazzo, Cinzia Lucia
Abstract: The antimicrobial and antioxidant properties of honey are well-established and recently the potential of honey for biotechnological and food preservative applications appeared promising. According to that, the present study evaluated the sensory profile and the antimicrobial potential of honey samples produced in different phytogeographical zones, in the Sicilian areas, and obtained from five different floral sources (chestnut, eucalyptus, sulla, thyme, and citrus). The specific sensory fingerprint of the analyzed samples was assessed by artificial senses (E-Eye, E-Nose, and E-Tongue). In addition, the antimicrobial activity against Staphylococcus aureus ATCC 29213, Listeria monocytogenes ATCC 19114, Bacillus subtilis DSM 10, Escherichia coli ATCC 25922, Enterococcus faecalis ATCC 29212, Pseudomonas aeruginosa ATCC 9027, Salmonella enterica Typhimurium ATCC 14026, and Candida albicans ATCC 10231 was evaluated. Artificial senses allowed to confirm the impact of climate factors and genetic features on honey composition suggesting implications for antimicrobial activity. A broad spectrum of antagonistic activity was displayed by the analyzed honey samples in both undiluted and diluted formulations. In particular, thyme honey showed interesting antagonistic features. In addition, a greater inhibitory effect of amber-colored honey than light ones was observed.